Numerical Simulation on Self-Propulsion Characteristics of Bionic Flexible Foil Considering Ground Wall Effect - Yongcheng Li; Nan Zhang; Xinyuan Tang; Ziying Pan; Pengfei Xu (Biomimetics)
In order to figure out the wall effect on the propulsive property of an auto-propelled foil, the commercial open-source code ANSYS Fluent was employed to numerically evaluate the fluid dynamics of flexible foil under various wall distances. A virtual model of NACA0015 foil undergoing travelling wavy motion was adopted, and the research object included 2D and 3D models. To capture the foil’s moving boundary, the dynamic grid technique coupled with the overlapping grid was utilized to realize the foil’s positive deformation and passive forward motion. The ground wall effect on fluid dynamics (thrust force, lift force and propulsive efficiency) and the flow structures of travelling wavy foil were analyzed. The numerical results show that the existence of the ground wall is beneficial for the propulsive property of foil. Specifically, the existence of the wall can improve the forward speed and efficiency of foil, with a maximum increase of 13% in moving velocity and a 10.5% increase in propulsive efficiency. The conclusions acquired in the current study are of great significance for the design of bionic UUV.